Sensing Techniques on Determination of Chlorine Gas and Free Chlorine in Water - Janudin, Nurjahirah; Kasim, Noor Azilah Mohd; Knight, Victor Feizal; Halim, Norhana Abdul; Noor, Siti Aminah Mohd; Ong, Keat Khim; Yunus, Wan Md Zin Wan; Norrrahim, Mohd Nor Faiz; Misenan, Muhammad Syukri Mohamad; Razak, Mas Amira Idayu Abdul; Ahmad, Muhammad Zamharir; Yaacob, Mohd Hanif (WILEY, 2022)
Chlorine gas is a greenish-yellow gas that is one of the most utilized gases in numerous industrial fields. It has been categorized as a choking agent that can threaten human, animal, and environmental safety. Currently, development of highly sensitive, selective, and precise chlorine sensors receives much attention. This review focuses on several sensing techniques used for chlorine gas and free chlorine in water. The fundamental working principles, as well as the sensing mechanisms of chlorine detection covering spectrophotometric, electrochemical, and optical techniques, are described. A comparison of various sensing materials is also discussed. Finally, an overview of the future improvements needed of high-performance chlorine sensors was suggested.
Keywords: WALLED CARBON NANOTUBES; CONDUCTING POLYMER; SELECTIVE DETECTION; HIGH-SENSITIVITY; ELECTROCHEMICAL DETECTION; TERNARY NANOCOMPOSITE; ZINC PHTHALOCYANINE; HIGHLY EFFICIENT; SENSOR; FERRITE; Engineering; Instruments & Instrumentation